2013
DOI: 10.1126/science.1244682
|View full text |Cite
|
Sign up to set email alerts
|

Giant Convection Cells Found on the Sun

Abstract: Heat is transported through the outermost 30% of the Sun's interior by overturning convective motions. These motions are evident at the Sun's surface in the form of two characteristic cellular structures: granules and supergranules (~1000 and ~30,000 kilometers across, respectively). The existence of much larger cells has been suggested by both theory and observation for more than 45 years. We found evidence for giant cellular flows that persist for months by tracking the motions of supergranules. As expected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
105
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(128 citation statements)
references
References 17 publications
19
105
1
3
Order By: Relevance
“…Although detection of giant cells in the Sun has been reported (e.g. Hathaway et al 2013), local time-distance helioseismology appears to indicate a gaping discrepancy between the Sun and current global simulations in that the latter produce significantly too much power at large scales (Hanasoge et al 2012). Local ring-diagram helioseismology, on the other hand, gives much larger convective velocities (Greer et al 2015).…”
Section: Discussionmentioning
confidence: 91%
“…Although detection of giant cells in the Sun has been reported (e.g. Hathaway et al 2013), local time-distance helioseismology appears to indicate a gaping discrepancy between the Sun and current global simulations in that the latter produce significantly too much power at large scales (Hanasoge et al 2012). Local ring-diagram helioseismology, on the other hand, gives much larger convective velocities (Greer et al 2015).…”
Section: Discussionmentioning
confidence: 91%
“…It is thus highly relevant if one can show that the generation of the differential rotation of the solar convection zone is based on the existence of nondiffusive Λ terms in the Reynolds stress in a similar sense to the solar dynamo being based on the existence of nondiffusive α terms in the induction equation. We argue that the Λ effect in rotating anisotropic turbulence is indeed needed to explain the current observation of positive (negative) horizontal cross correlation Q θφ in the northern (southern) hemisphere at the solar surface, which Hathaway et al (2013) indicated as a result of the proper motions of giant cells. All analytical and numerical studies lead to positive functions H, which in the bulk of the convection zone are able to overcompensate for the diffusive term, which alone would lead to the signs that are not observed.…”
Section: Discussionmentioning
confidence: 99%
“…According to (1), an accelerated equator provides a negative (positive) horizontal Reynolds stress in the northern (southern) hemisphere. From the data of the Helioseismic and Magnetic Imager (HMI) onboard the Solar Dynamics Observatory (SDO), Hathaway et al (2013) have recently isolated a giant cell pattern at the solar surface where the proper motions form a horizontal cross-correlation Q θφ , which is -as a fulfilled necessary condition -antisymmetric with respect to the equator. The correlation is positive (negative) at northern (southern) midlatitudes, and its amplitude of 20 m 2 /s 2 suggests rms velocities of the cells of (say) 10 m/s (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This argument may be too naive and would obviously be in conflict with the results of Greer et al (2015), which show an increase with depth at low spherical harmonic degrees. On the other hand, Bogart et al (2015) have argued that the flows reported by Hathaway et al (2013) may be non-convective in nature and, in fact, magnetically driven and perhaps related to the torsional oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that small flow speeds of giant cell convection have been found by correlation tracking of super-granule proper motions (Hathaway et al 2013). The typical velocities are of the order of 20 m s −1 at spherical degrees of around 10.…”
Section: Introductionmentioning
confidence: 99%